Bots vs. humans: how schema congruity, contingency-based interactivity, and sympathy influence consumer perceptions and patronage intentions. Issue 4 (19th May 2022) - Lou, Chen; Kang, Hyunjin; Tse, Caleb H.
Abstract: Artificial intelligence (AI) is rapidly reconstructing consumer experiences with brands in recent years. However, there have been the unsettled debates on whether humans react to robots (e.g., chatbots) in the same way as they do to other humans, and how the intrinsic strength of AI (i.e., autonomous processing and synthetization of information) and humans (i.e., emotional intelligence) factor in the human-AI interactions in brand communication settings. Hence, this study investigates the conditions under which a service entity of a brand can optimize their potential. To this end, the current study conceptualizes and operationalizes two dimensions that define chatbots' capabilities – message contingency (i.e., contingency-based interactivity) and emotional intelligence (i.e., sympathy). Based on two experiments, we found that, regarding the same online customer service of an apparel brand, participants rated the human employee to be more competent and warmer than a chatbot. When a human employee who expresses sympathy to the afflicted customer during the conversation, participants considered the employee to be more competent when he/she also exhibits contingency (vs. no contingency) during the conversation, which in turn, elicited higher patronage intentions among participants.